Pakan Aditif Ekstrak Etanol Lumut Hati Meningkatkan Pertumbuhan Morfologi Duodenum dan Perkembangan Otot Dada Ayam Pedaging (SUPPLEMENTATION OF ETHANOLIC EXTRACT OF MARCHANTIA IN PRE-STARTER DIET IMPROVES THE GROWTH OF DUODENUM AND PECTORALIS THORACICUS - Saragih, Hendry Tri Sakti Surya Gunawan; Alawi, Muhammad Faisal; Rafieiy, Muhammad; Lesmana, Indra; Sujadmiko, Heri (Jurnal Veteriner, 2018)
This study aimed to determine the effectiveness of ethanolic extract of Marchantia as an alternative additive in broiler’s chicken feed. The research was designed by using 5 treatment groups with 20 day-old chick broilers in each group and the treatment was done until the sample aged 14 days. The treatment groups consisted of basal feed and ethanolic extract of Marchantia in 0; 62.5; 250; 500; 1000 mg/kg basal feed. Data were analyzed by using one way ANOVA test followed by Tukey test with significance P <0.05. The results showed that at 14 days old of the sample, the weight gain of the broilers in the treatment group 1, 2, 3, and 4 were higher than the control group; Feed Conversion Ratio of treatment group 4 was better than the control group and other treatments; the small intestine morphology of villus heights, crypt depth, and villus/crypt ratio showed that the treatment group 3 and 4 were better than the control group; the pectoralis muscle’s weight, muscle’s area, and myofiber’s area showed that the treatment group 1 and 3 were better than the control group. The study indicates that the ethanolic extract of Marchantia spp. with concentration of 750-1000 mg/kg basal feed has effective ability as an alternative additive in broiler’s chicken feed.